Diagnostic utility of additional whole-chest CT as part of an acute abdominal pain CT imaging pathway during the COVID-19 pandemic. Issue 8 (August 2020) - Hamilton, N.E.; Adam, G.H.; Ifan, D.L.; Lam, S.S.; Johnson, K.; Vedwan, K.A.G.; Shambrook, J.S.; Peebles, C.R.; Harden, S.P.; Abbas, A.
Abstract : Aim: To evaluate the diagnostic utility of additional whole-chest computed tomography (CT) in identifying otherwise unheralded COVID-19 lung disease as part of an acute abdominal pain CT imaging pathway in response to the COVID-19 pandemic. MATERIALS AND METHODS: Consecutive patients ( n =172) who underwent additional whole-chest CT via a COVID-19 acute abdominal pain CT imaging pathway between 27 March and 3 May 2020 were evaluated in this retrospective single-centre study. Chest CT examinations were graded as non-COVID-19, indeterminate for, or classic/probable for COVID-19. CT examinations in the latter two categories were further divided into one of three anatomical distributions (lung base, limited chest [below carina], whole chest [above carina]) based on location of findings. Reverse transcriptase-polymerase chain reaction (RT-PCR) results and clinical features of COVID-19 were assessed to determine if COVID-19 was clinically suspected at the time of CT referral. RESULTS: Twenty-seven of the 172 (15.7%) patients had CT features potentially indicative of COVID-19 pneumonia, 6/27 (3.5%) demonstrating a classic/probable pattern and 21/27 (12.2%) demonstrating an indeterminate pattern. After correlation with clinical features and RT-PCR 8/172 (4.7%) were defined as COVID-19 positive, of which only 1/172 (0.6%) was clinically unsuspected of COVID-19 at the time of CT referral. All COVID-19 positive cases could be identified on review of the lung base alone. CONCLUSION: Whole-chest CT as part of an acute abdominal pain CT imaging pathway has a very low diagnostic yield for our cohort of patients. All COVID-19-positive patients in our cohort were identified on review of the lung bases on the abdominal CT and this offers an alternative imaging approach in this patient group. Highlights: Low unheralded COVID-19 diagnostic rate for whole chest CT for acute abdominal pain Alternative CT strategies for COVID-19 diagnosis in acute abdominal pain are viable Mean radiation dose burden of 3.4mSv for additional whole chest CT for COVID-19